SME productivity stakeholders: getting in the right orbit. Issue 2 (28th April 2020) - Jones, Oliver William; Gold, Jeff; Devins, David
Abstract : Purpose: The purpose of this paper is to explore who small and medium-sized enterprise (SME) owner–managers consider as key stakeholders for their business for helping increase productivity and the nature of the stakeholders' impact. Design/methodology/approach: The study uses the Lego Serious Play methodology and narrative analysis in a focus group setting. Findings: The analysis revealed a narrow depth of field of productivity stakeholders and identified critical narratives, involving close stakeholders which could constrain productivity. Lack of information on current and/or future productivity states, and a social brake due to the potential impact on employees are two at the forefront of owner–manager perspectives. The study also identified the importance of internal and external champions to improve productivity and re-enforced the significance of skills gaps, the role of Further Education providers and other infrastructure assets. Research limitations/implications: The purposiveness sample of the single focus group setting results in a lack of generalizability, but provides potential for replication and transposability based on the generic type of stakeholders discussed. The work highlights the potential to further enhance the constituent attributes of stakeholder salience. Practical implications: There is a potential for different network agents to increase their collaboration to create a more coherent narrative for individual productivity investment opportunities and for policy makers to consider how to leverage this. Social implications: The findings suggest that the implications of deskilling and job loss are major factors to be considered in the policy discourse. SMEs are less likely to pursue productivity improvements in a low growth setting because of their local social implications. Originality/value: The study is innovative in using Lego to elucidate narratives in relation to both stakeholder identification and their contributions to productivity improvement impact in a UK SME context. The study introduces an innovative stakeholder orbital map and further develops the stakeholder salience concept; both useful for the future conceptual and empirical work.